SINTESIS DAN SIFAT MEKANIK BIOKOMPOSIT SERAT HELICONIA-POLIESTER - Akhiruddin Maddu (Jurnal Biofisika, 2012)
In this study, polyester-fiber heliconia biocomposites has been created and tested on its mechanical properties. Biocomposites was manufactured begins by separating the fibers. it consists of three stages, namely chlorization, alkaline leaching and extraction. After that, the manufacture of composites made with Hand Lay-up techniques. Three samples with variations in fiber content, ie without the addition of fiber, 0.54 g and 2.08 g fiber. Characterization of samples includes tensile test, hardness, and impact. The test results known that the tensile strength and hardness increased with increasing the amount of fiber heliconia. Impact test shows sample values optimum working temperature is 10°C